2017
DOI: 10.1021/acs.inorgchem.7b02238
|View full text |Cite
|
Sign up to set email alerts
|

Redox Noninnocent Azo-Aromatic Pincers and Their Iron Complexes. Isolation, Characterization, and Catalytic Alcohol Oxidation

Abstract: The new redox-noninnocent azoaromatic pincers 2-(arylazo)-1,10-phenanthroline (L) and 2,9-bis(phenyldiazo)-1,10-phenanthroline (L) are reported. The ligand L is a tridentate pincer having NNN donor atoms, whereas L is tetradentate having two azo-N donors and two N-donor atoms from the 1,10-phenanthroline moiety. Reaction of FeCl with L or L produced the pentacoordinated mixed-ligand Fe(II) complexes FeLCl (1) and FeLCl (2), respectively. Homoleptic octahedral Fe(II) complexes, mer-[Fe(L)](ClO) [3](ClO) and mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 105 publications
2
75
0
Order By: Relevance
“…Recent studies on azo-containing pincer ligands have shown that also alcohol dehydrogenation can be catalyzed via a pathway that involves a reduced azo moiety. 11 Similarly, studies on molecular electrocatalysts for the hydrogen evolution reaction (HER) have identified several systems in which the mechanism does not involve “traditional” metal hydride intermediates; 12 instead, the organic ligand is proposed to be involved as the locus of reduction, protonation, or both. Thus, the assembly of two protons and two electrons as required for H 2 production requires a delicate interplay between the reactivity of the metal center and that of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on azo-containing pincer ligands have shown that also alcohol dehydrogenation can be catalyzed via a pathway that involves a reduced azo moiety. 11 Similarly, studies on molecular electrocatalysts for the hydrogen evolution reaction (HER) have identified several systems in which the mechanism does not involve “traditional” metal hydride intermediates; 12 instead, the organic ligand is proposed to be involved as the locus of reduction, protonation, or both. Thus, the assembly of two protons and two electrons as required for H 2 production requires a delicate interplay between the reactivity of the metal center and that of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Redox-active, or 'noninnocent', ligands have more energetically-accessible levels that allow redox reactions to change their charge state [11]. In recent decades, noninnocent (or redox) ligands have been intensively studied for their unusual chemical behavior [12][13][14][15][16][17][18][19][20][21][22][23]. "Introduced in the late sixties, noninnocent (or redox) ligands have been extensively studied for their unusual and intriguing chemical behavior.…”
Section: Metal Complexes Containing Redox-active Ligandsmentioning
confidence: 99%
“…Redox-active ligands range from the small archetypical NO +/•/− and O 2 0/•−/2− systems via the classical 1,4-dihetero-1,3-diene chelates (e.g., α-diimine, dithiolene, or o-quinone redox series) to π-conjugated macrocycles. [15,22,23]. Currently, catalytic systems based on transition metal complexes (Rh, Ru, Pt, Pd, etc.)…”
Section: Metal Complexes Containing Redox-active Ligandsmentioning
confidence: 99%
“…Such studies are particularly important with respect to the reliability of the B3LYP functional, which has been applied in countless related systems. [18][19][20][21][22][35][36][37][38]41,[43][44][45][50][51][52][53][66][67][68][69][70][71] A further point deserves attention with respect to the use of mono-reference DFT methods to study these compounds. It is known that static correlation can influence the electronic structure of transition metal complexes having non-innocent ligands, 48,52 notably in the case of iron complexes.…”
Section: Introductionmentioning
confidence: 99%